Philipp of Harveng's Writings for Religious Instruction (Quinque Responsiones): New Observations on their Transmission, with an Edition of the Previously Unknown Prologue to the Responsio de Silentio - Breitenstein, Antry Mirko (Analecta Praemonstratensia, 2021)
Keywords: 👤 philip of harvengt

Was ein Prämonstratenser wissen muss. Philipp von Harveng und sein Werk "Über die Unterweisung der Kleriker" - Breitenstein, Mirko (Mit Bibel und Spaten. 900 Jahre Prämonstratenser-Orden, 2021)
Keywords: 👤 philip of harvengt

Filip van Harvengt, tweede abt van Bonne-Espérance - Wouters, Jos (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: 👤 philip of harvengt

Drei Augustinus-Biographien des XII. Jahrhunderts: Ivo von Chartres, Rupert von Deutz, Philipp von Harvengt - Stiene, Heinz Erich (Hiersemann Verlag, 2019)
Keywords: 👤 philip of harvengt

Philip of Harvengt's Life of the Blessed Virgin Oda - Robertson, Lynsey (Journal of Medieval History, 2010)
For every famous author of the twelfth-century renaissance, there are numerous lesser-known writers. Despite being overshadowed by more brilliant scholars or those closer to the centre of important events, their voices add depth to the study of the intellectual and religious history of this period. A founding member of one of the earliest Premonstratensian houses, a highly-educated and prolific author, much in demand as a hagiographer, and a vigorous defender of the clerical order, Philip of Harvengt is one such writer, and a worthy subject for study. This article examines one of his hagiographical works, the Life of the Blessed Virgin Oda, a nun attached to his own house, whom he portrays as a martyr. It analyses the predominant and recurrent concerns and ideals expressed in the Life, particularly the claim to martyrdom, and the means by which this is expressed.
Keywords: 👤 philip of harvengt

An analysis of the correspondence and hagiographical works of Philip of Harvengt - Robertson, Lynsey E. (University of St Andrews, 2008)
For every famous author of the twelfth-century renaissance, there are numerous lesser-known writers. Despite being overshadowed by more brilliant scholars or those closer to the centre of important events, their voices add depth to the study of the intellectual history of this period. A founding member of one of the earliest Premonstratensian houses; a highly-educated and prolific author, much in demand as a hagiographer; and a vigorous defender of the clerical order, Philip of Harvengt is one such writer, and a worthy subject for study. This thesis examines two bodies of Philip’s works – his letters and his hagiographical writings – analysing the predominant and recurrent concerns and ideals expressed in them, and the means by which they are expressed. The letters are carefully crafted works, examples of the literary labour which Philip writes is incumbent upon the cleric. The first part of this thesis approaches these letters in chapters on four themes: the role of the ecclesiastical prelate; the importance of learning; the relationship between religious orders; and Philip’s use of the motif of friendship. His hagiographical works, too, are examples of literary artistry, to move as well as to educate the audience. In the second part of the thesis, these will be discussed individually, with the first chapter analysing his vita of Oda, a nun attached to his own house, whom he portrays as a martyr. The succeeding chapters consider Philip’s rewritings of earlier vitae, and show how he managed his sources in order to produce vitae depicting their subjects according to his ideal model of sanctity. Philip’s letters express concerns shared by contemporaries, reflecting anxieties surrounding roles and ideal forms of living in a period immediately following the first fervour of religious renewal. His hagiographies articulate ideals of sanctity, clarifying these when they are not made sufficiently explicit in earlier works, for the better edification of an audience pursuing this vita perfecta. Both letters and hagiographies are designed to exhort and instruct the reader or listener: above all, Philip is a teacher.
Keywords: bonne-espérance; 👤 philip of harvengt

Philippe de Harveng, abbé de Bonne-Espérance au XIIe siècle, et la conduite des clercs de son temps - Negri, Franca (Abbatiat et abbés dans l'ordre de Prémontré, 2005)
Keywords: bonne-espérance; 👤 philip of harvengt

Augustinusregel, professio canonica und Prämonstratenser im 12. Jahrhundert. Das Beispiel der Norbert-Viten, Philipps von Harvengt und Anselms von Havelberg - Bomm, Werner (Regula Sancti Augustini. Normative Grundlage differenter Verbände im Mittelalter. Tagung der Akademie der Augustiner-Chorherren von Windesheim und des Sonderforschungsbereichs 537, Projekt C "Institutionelle Strukturen religiöser Orden im Mittelalter" vom 14. bis zum 16. Dezember 2000 in Dresden, 2002)
Keywords: 👤 anselm of havelberg; 👤 norbert of xanten; 👤 philip of harvengt

„Deo militans clericus“. Rittertum und Krieg im Werk Philipps von Harvengt - Leinsle, Ulrich G. (Analecta Praemonstratensia, 2001)
The view of knighthood and war in the work of Philipp of Harvengt is ambivalent. Essentially to a spiritual interpretation is the biblical typology (especially Ehud, David, Joshua, Judas Maccabaeus). Philipp does not dissolve the medieval class structure of the three ordines, but emphasizes the pre-eminence of the clergy. Chivalry has to serve the Church, which is quite usual for authors of the Gregorian Reform. However, a difference between class and behaviour can be observed regarding to both knights and monks. Monastic behaviour is transferred to the secular ideal of the miles litteratus; by literary education in the school, a knight becomes a clericus. Chivalry and war cannot simply be used as models of reflection in canonical life and spiritual warfare, while some knightly virtues, founded in biblical imagery, are important for the spiritual warfare in the monastery, especially bravery and obedience. Literary education and holiness are principles which superseded the rigid medieval class structure.
Keywords: 👤 philip of harvengt

Schola claustrum alterum dici debet. Filip van Harvengts raadgevingen aan studenten - Wouters, Jozef (Analecta Praemonstratensia, 2000)
In his letters to students, Philip of Harvengt († 1183) engages himself in a dialogue with the environment of the schools of his time. This is obvious since the exchange of letters was not an entirely private affair as it is nowadays. Letters were shared with one's companions and read by them. When Philip therefore wrote a letter to a student, he addressed in fact a broader public. The letters addressed to students appear to belong to two different literary types. His earliest letters, Ad Wedericum and ad Hervardum are in fact treatises concerning a debated question with some spiritual advise in the margin. Later written letters only contain spiritual advise. But all Philip's letters show a keen awareness of the fact that a sound exegesis starts from a litteral understanding of the material text of Sacred Scripture, even though he depicts its study as preparing for an experienced meeting with the One who inspired it. This fundamental conviction concerning study of Scripture probably points towards influence from the Parisian school of the canons regular of Saint Victor. In his letter Ad Wedericum Hugh of Saint Victor is explicitly quoted while Philip develops his argument in favour of a literal explication of the six days during which creation took place according to the book Genesis. "The school should be called another monastery", for, in spite of the different environment, assiduous study of Scripture is performed in both places. Bible study probably took on a different character in monasteries of regular canons, such as Saint Victor in Paris and Bonne-Espérance, than the monastic lectio divina.
Keywords: 👤 philip of harvengt

Philip of Harvengt's Vita Augustini : the medieval premonstratensians and the patristic model - Neel, Carol (Analecta Praemonstratensia, 1995)
Keywords: 👤 philip of harvengt

Philip of Harvengt and Anselm of Havelberg: The Premonstratensian Vision of Time - Neel, Carol (Church History: Studies in Christianity and Culture, 1993)
Keywords: 👤 anselm of havelberg; 👤 philip of harvengt

Philip of Harvengt and Anselm of Havelberg: the Premonstratensian vision of time - Neel, Carol Leigh (Church history, 1993)
Keywords: 👤 anselm of havelberg; 👤 philip of harvengt

Spiritus sanctus et B. Deipara-Virgo apud ductores Praemonstratenses saeculi duodecimi, potissimum apud Philippum de Harvenig - Valvekens, Johannes B. (Analecta Praemonstratensia, 1981)
Keywords: 👤 philip of harvengt; 📚 premonstratensian (general)

A propos des Instructions pour les clercs (De Institutione clericorum) de Philippe de Harveng - Weyns, Nobert J. (Analecta Praemonstratensia, 1977)
Keywords: 👤 philip of harvengt

Philip of Harvengt's contribution to the question of passage from one religious order to another - Roby, Douglass (Analecta Praemonstratensia, 1973)
Keywords: 👤 philip of harvengt

Filips van Harveng, (ca. 1100-1183), abt, schrijver - Weyns, Nobert J. (Nationaal biografisch woordenboek, 1970)
Keywords: bonne-espérance; 👤 philip of harvengt

L'ideale di vita sacerdotale presso Filippo di Harveng - Vetri, M. (Analecta Praemonstratensia, 1961)
Keywords: 👤 philip of harvengt

Philippe de Harveng's Logogrypha et Aenigmata: An Unfinished Decipherment - Mahoney, John F. (Medievalia et Humanistica, 1958)
Keywords: 👤 philip of harvengt

Saint Bernard de Clairvaux et Philippe de Hareng - Delhaye, Philippe (Buletin de la société historique et archéologique de Langres, 1953)
Keywords: 👤 philip of harvengt

Deiparae Assumptio apud Philippum de Harvengt et Adamum Scotum - Valvekens, Johannes B. (Analecta Praemonstratensia, 1953)
Keywords: 👤 adam of dryburgh; 👤 philip of harvengt

De leer over de erfzonde bij Philippe van Harveng - Sijen, G. P. (Analecta Praemonstratensia, 1941)
Keywords: 👤 philip of harvengt

Les oeuvres de Philippe de Harveng, Abbé de Bonne-Espérance - Sijen, G. P. (Analecta Praemonstratensia, 1939)
Keywords: 👤 philip of harvengt

La possibilité du Christ chez Philippe de Harveng - Sijen, G. P. (Analecta Praemonstratensia, 1938)
Keywords: 👤 philip of harvengt

Philippe de Harveng, abbé de Bonne-Esperance - Sijen, G. P. (Analecta Praemonstratensia, 1938)
Keywords: bonne-espérance; 👤 philip of harvengt

Philippe de Harvengt, abbé de Bonne-Espérance - Berlière, Ursmer (Revue bénédictine, 1892)
Keywords: bonne-espérance; 👤 philip of harvengt